Peran Resiliensi dan Iklim Organisasi terhadap Work Engagement - Nurlintang Fitri Listya Astika; Ridwan Saptoto (Gadjah Mada Journal of Psychology (GamaJoP), 2016)
The uncertain state of the mining industry has impacts to the declining of thedemand for the heavy equipment industry sector. One of the effort to keep the companysurvive to face the challenge is improving the quality of production. This essential effort can beachieved by enhancing work engagement. This study aims to determine the role of resilienceand organizational climate on work engagement. The hypothesis of this study was: resilienceand organizational climat simultaneously predict the work engagement. The subjects for thisresearch were 63 employees in PT. Komatsu Indonesia. The instrument in collecting the datawas a questionnaire. The result of the multiple regression shows that this study’s hypothesis isrejected. Resilience and organizational climate cannot simultaneously predict the workengagement. Resilience can significantly predict work engagement by p=0.004 (p<0.05), butorganizational climate cannot significantly predict it as seen in p=0.235 (p>0.05).